Раннепифагорейская астрономия в свете китайских параллелей [Dmitri Panchenko: Early Pythagorean Astronomy in the Light of Chinese Parallels] - Панченко, Д. В. (Hyperboreus, 2014)
Late authors, Iamlichus, Proclus and Simplicius, attribute to the Pythagoreans the invention of epicycles and eccentric circles. The evidence was accepted by B. L. Van der Waerden, but repeatedly denied by the majority of scholars. The parallels found in Chinese treatise The Zhou bi suan jing help to see that the ideas of epicycles and eccentric circles were indeed familiar to early Greek astronomy of Anaximenian type, though they were designed and used in a way different from that of the late Greek astronomy. They could have been found in a work by one of early mathematikoi. Since there was a tradition according to which Pythagorean scientists were collectively also named mathematikoi, the ideas of the former group could have been attributed to the latter, and possibly not without a reason.